Importance of the OEKO-TEX 100 Standard for the Textile Industry (Texas Journal of Engineering and Technology, 2022)
In this article, the introduction of the OEKO-TEX 100 standard, which is today's international certificate for the production of textile products to the world market, and its possibilities, the essence of the OEKO-TEX 100 standard, the product produced in an environmentally friendly way and about the role and importance of textile products processed in ecologically clean borders in the world production